Formation of Spritual and Social Attitudes in ‎Akidah Akhlak Subjects at Islamic Junior High ‎School - Bima Fandi Asy'arie; Muhammad Fadhlan; Deliar Agha Firdaus; Mahendra Utama Cahya Ramadhan; Muhammad Hanif Abdillah (TADRIS: Jurnal Pendidikan Islam, 2023)
The formation of spiritual and social attitudes is an element that must be carried out in schools in Indonesia. The purpose of this study was to explain the design of the assessment of spiritual aspects and social attitudes of students in the subject of morals and faith. To analyze the obstacles encountered in carrying out the assessment of the spiritual aspects and social attitudes of students at MTs Negeri 1 Lampung Timur. This research is a qualitative research with field research (Field research). Methods of data collection through observation, in-depth interviews, and documentation. After the data was obtained, the researchers analyzed the data using the Miles and Huberman and Saldana approaches, namely in four ways (1) collecting data, (2) combining data, (3) condensing data, (4) and concluding data. The research was conducted in class VIII MTs Negeri 1 Lampung Timur on the subject of moral aqeedah. Interviews were held with two eye teachers. The results of this study are as follows: 1) The formation of spiritual and social attitudes in students has been successfully carried out through planning that begins with the help of core needs and basic needs, uses spiritual attitude techniques, fills out research instruments, and fills out journals, 2) Teachers of character have identified KI and KD, towards the assessment of spiritual attitudes and social attitudes according to KI-1, KI-2 and KD before learning is carried out. There is collaboration with teachers of other subjects (teachers in class and homeroom), 3) there are variations made by Akidah Akhlak teachers in forming spiritual attitudes such as interpreting greetings when entering the classroom, starting learning with prayer, reading sholawat of the Prophet Muhammad SAW , and doing tadarus juz 30, 4) habituation of social attitudes carried out by the teacher, namely holding prayers and cleaning the school environment.